Community development venture capital: concept and status quo in Germany - Ann-Kristin Achleitner; Reiner Braun; Marko Bender; Annabell Geidner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2008)
As most other countries, Germany also faces dramatic regional differences in terms of socioeconomic development. One important driver of such development is the existence of a healthy entrepreneurial activity and the creation of new companies. We argue that venture capital (VC) and especially community development venture capital (CDVC) can be a powerful instrument to stimulate entrepreneurship and to support the growth of ambitious companies. Hence, the present paper deals with the general questions, whether there are regional gaps in the supply of VC in Germany? Whether these regional gaps do geographically correspond to the most deprived areas in Germany, and which kind of VC companies are currently in place in order to close potential regional gaps? Geographically, we find that the north-eastern part of Germany is far more deprived than the rest of the country, but is relatively well supplied with VC. Nevertheless, the primary potential target area for CDVC activities in the country is the federal state of Brandenburg in this area. Our assessment of German players in the VC market reveals that some public VC companies do investments similar to CDVC. However, these companies do not offer real hands-on support for entrepreneurs, and real CDVC engagement in the country is yet to come.
Keywords: G24; O16; 330; regional development; community development venture capital; regional equity gap; Regionale Entwicklung; Regionalpolitik; Risikokapital; Regionale Disparität; Deutschland